Implementing the Merdeka Belajar Policy through Deep Learning: A Case Study in Social Studies Education in Bima Regency - Muhammad Yamin; Abdul Wahab; Lutfin Haryanto; Faidin Faidin (STAI Hubbulwathan Duri, 2025)
This study examines the effectiveness of Indonesia’s Merdeka Belajar (Freedom to Learn) policy through the implementation of deep learning strategies in Social Studies education within Bima Regency, a socio-economically constrained region. The policy promotes student-centered learning, autonomy, and contextual relevance—principles that align closely with deep learning pedagogy. A qualitative multiple case study design was employed in two junior high schools. Data were collected through in-depth interviews with ten teachers and thirty students, twenty-four classroom observations, and analysis of planning documents and student work samples. Thematic analysis was conducted using an inductive-deductive coding approach to identify patterns related to student engagement, critical thinking, and pedagogical transformation. Findings revealed a substantial increase in student engagement, with 90% actively participating in group discussions and 70% successfully formulating solutions to social problems. Student feedback indicated strong preference for project-based learning (73%) and the Merdeka Belajar model (83%). Teachers reported increased student motivation, though only 70% demonstrated full understanding of the curriculum's core principles. Document analysis showed partial integration of local context and 21st-century competencies. Key barriers included inadequate digital infrastructure and limited teacher training. These results suggest that the integration of Merdeka Belajar and deep learning can effectively foster critical thinking and participatory learning in under-resourced settings. However, successful and sustainable implementation requires systemic support through infrastructure investment and targeted professional development.